Spotlight on USA - Falk, Randee (Oxford University Press, 1993)
Travel from region to region with this book, learning about culture, history, and everday life in the United States. Explore the natural wonders of the West, shop the streets of New York and Los Angeles, or float down the Mississippi River in a raft. From the wilderness of Alaska to the sunshine of Key West, from Elvis to the Alamo, Spotlight takes you there.